Impact of obstructive sleep apnea on neurological recovery after ischemic stroke: A prospective study. (15th February 2017) - Menon, D.; Sukumaran, S.; Varma, R.; Radhakrishnan, A.
Abstract : Objectives: The presence of obstructive sleep apnea (OSA) has been found to adversely affect the neurological recovery after acute ischemic stroke (AIS) in previous observational studies. However, in most of these studies, diagnosis of OSA was based on oximetry data alone, raising concern in the accuracy of diagnosis as well as estimation of severity. Purpose of our study was to determine the prevalence and severity of OSA (based on polysomnography and American Association of Sleep Medicine [AASM] criteria) in patients with AIS and to compare the post‐stroke neurological and functional outcome, in those with and without OSA. Materials and Methods: A prospective single‐centre study was conducted over a period of eighteen months from January 2013. The demographic and clinical data were collected, and the etiology of stroke was classified according to TOAST classification. Subsequently, all selected patients (N=99) underwent premorbid sleep status assessment by Epworth Sleepiness Scale followed by polysomnography using Resmed ApneaLink polysomnograph. Data were analyzed to find out the prevalence and severity of OSA as well as its impact on neurological recovery as assessed by National Institutes of Health Stroke Scale (NIHSS) and modified Rankin scale (mRS) at different time points, starting from admission. Results: There was a high prevalence of OSA ( 60%) with a quarter of them having severe OSA. The OSA group had a significantly higher mean NIHSS score at discharge ( P =.002) and significantly higher mRS score (irrespective of severity of OSA) at all points of evaluation. Conclusion: Ischemic stroke patients with OSA tend to have poor neurological and functional recovery, across all segments of stroke and OSA severity.